2020
DOI: 10.1007/s13187-020-01806-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vaccination Interventions to Promote HPV Vaccine Uptake Rates in a College-Aged Population: a Systematic Review

Abstract: This systematic review provided synthesized evidence regarding the effectiveness of the interventions promoting the human papillomavirus (HPV) vaccination in college-aged population. The HPV infection is the most prevailing sexually transmitted disease. Despite the availability and effectiveness of the 9-Valent HPV vaccine, the vaccine coverage among young adults remained low. In witness to the increasing burden of HPV-related infections and cancers, research focused on the vaccination interventions should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
(65 reference statements)
3
14
1
Order By: Relevance
“…This confirms results from previous reports. 11 [15][16][17] In our study, we only saw a trend towards a small difference in HPV vaccine knowledge between the younger and older age groups. Other studies, however, found a higher knowledge score in older compared with younger participants.…”
Section: Discussioncontrasting
confidence: 52%
“…This confirms results from previous reports. 11 [15][16][17] In our study, we only saw a trend towards a small difference in HPV vaccine knowledge between the younger and older age groups. Other studies, however, found a higher knowledge score in older compared with younger participants.…”
Section: Discussioncontrasting
confidence: 52%
“…Exposure to antivaccine content on social media has been associated with delays in and refusal of vaccination [3]. While the development of tailored messages (eg, text messages) has increased immunization rates [10], public provaccine campaigns via social media have yielded limited success, as shown in several systematic reviews of interventions for various vaccines [4,[11][12][13][14][15][16][17][18][19]. Given that there is a methodological barrier to assessing the impact of public campaigns on regional immunization rates, the current literature has not yet fully explicated how the antivaccine movement continues to engage and persuade the public to deny immunization despite provaccine advocates' counteracting efforts.…”
Section: Background and Specific Aimsmentioning
confidence: 99%
“…Even before the COVID-19 vaccination program started in the US, interventions to increase immunization rates were a focus of systematic reviews to counteract declining immunization rates ( Asare et al, 2021 , Crocker-Buque et al, 2017 ; Falcone, 2019; Jarrett et al, 2015 , Lott et al, 2020 , Niccolai and Hansen, 2015 , Nour, 2019 , Odone et al, 2015 , Ortiz et al, 2019 , Ou and Youngstedt, 2020 , Smulian et al, 2016 ). However, most of these reviews focused on narrow regions or clinician–patient communication, and thus their findings are not directly applicable to social media–based intervention campaigns disseminated to broader audiences.…”
Section: Introductionmentioning
confidence: 99%